POLITIK IDENTITAS DAN WARISAN KOLONIAL DALAM NOVEL PULANG KARYA LEILA S. CHUDORI: POSTKOLONIAL HOMI K BHABA - Nensilianti; Ridwan; Nur Ainun Pratidina (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
This study analyzes the politics of identity and colonial legacy in the novel Pulang by Leila S. Chudori using a postcolonial theory approach, particularly the concepts of Homi K. Bhabha. The novel depicts the experiences of political exiles after the events of 1965, who are forced to live in exile and face identity crises. Using a descriptive qualitative method, this study explores how colonialism and political repression shape the characters' social reality and how their identities are dynamic and negotiated in hybrid and ambivalent spaces. The results show that the novel “Pulang” reflects the impact of colonial legacies, which not only influence state policies and social structures but also shape the identities of individuals in liminal positions. Bhabha’s concepts of hybridity, ambivalence, and mimicry reveal the characters' struggles to shape their identities in the transnational realm. In this context, literature serves as a medium to create alternative narratives, challenge state hegemony, and reinterpret the meaning of Indonesian nationalism through a postcolonial framework